Розвиток лексичної сполучуваности детермінованої лексики на прикладі терміна інфекція - Куньч, Зоряна (Slavia Orientalis, 2025)
This research aims to analyze the development of lexical conjugation of deterministic lexemes in the journalistic style of the literary language, with the term infection employed as an example. The material for the research was the context of its use on the electronic news resource “Ukrainian Pravda” for the period 2020‑2022. The research methodology combines corpus and linguistic methods. Based on analysis of the material selected, we state that the term vocabulary becomes an integral part of journalistic discourse, organically functioning in it and testifying to a high level of its intellectualization. Thanks to the extensive involvement of deterministic lexemes, the authors achieve the maximum presentation accuracy and reproduce the linguistic realities of a modern educated society. The changes in the lexical conjugation of the lexeme infection, which we discovered as a result of this study, confirm that the term vocabulary contributes to the realization of the author’s creative ideas; deterministic vocabulary in journalistic discourse not only serves to denote relevant scientific concepts but also contributes to the creation of a specific stylistic effect, strengthening the artistic expressiveness, saturating a text with expression.